PENTINGNYAIMPLEMENTASI PROBLEM-BASED LEARNING DALAM MEMBENTUK SOFT SKILL COMPETENCY - Murniati, Dewi Eka (Prosiding Pendidikan Teknik Boga Busana, 2021)
A deep gap has been occurred between the graduate of higher education, especially vocational education, and the industry expectation. As industry is the primary stakeholders, students are expected to have a better representation in the industry for which they are being prepared. Job competencies relate not only with the work task, but also with soft skills and attitudes. Problem-based learning (PBL)facilitates the students to engage the development of problem-solving and analytical skills. Furthermore, PBL derives key soft skills, such as communication, teamwork, motivation, responsibility, work ethics, social relation, and time management. The more prolong use of PBL would generate higher levels of learner autonomy. However, conducting PBL in the curriculum is not without difficulties. Unclear goals within vocational department, teacher staff, and students are likely to be the most obstacles. Therefore, there is a need ofhigh commitment from vocational education party to achieve a more qualified outcome that is required in the work place. Keywords: problem-based learning, soft skill competency, implementation